Operative Strategy for Acute Type A Aortic Dissection: Ascending Aortic or Hemiarch Versus Total Arch Replacement With Frozen Elephant Trunk - Uchida, Naomichi; Shibamura, Hidenori; Katayama, Akira; Shimada, Norimitsu; Sutoh, Miwa; Ishihara, Hiroshi (The Annals of thoracic surgery, 2009)
This report compares long-term results with total arch replacement with frozen elephant trunk (FET) to ascending aortic or hemiarch replacement (AHR) for acute type A aortic dissection. The subjects were 120 consecutive patients, including 65 who received FET and 55 who had AHR for acute type A aortic dissection from 1997 to 2008. The late results after surgery were retrospectively compared between the FET and ARH groups. Three patients in the FET group died, and 2 patients in the AHR group died. In long-term follow-up (mean, 67 months), the survival rate after 5 years was 95.3% for the FET group and 69.0% for the AHR group ( p = 0.03). The event rate for the thoracic aorta after 5 years showed a significant difference between the FET and AHR groups (95.7% versus 73.0%, p = 0.01). A false lumen at the proximal descending aorta was patent in 16 patients (29%) in the AHR group, but it was thrombosed in all in the FET group. In patients with acute type A aortic dissection, it is possible to perform extensive primary repair using the FET technique with relative safety. FET may reduce the necessity for further operations to manage a residual false lumen.